2003
DOI: 10.1128/jcm.41.7.3043-3045.2003
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Human Metapneumovirus Infection in Young Children and Genetic Heterogeneity of the Viral Isolates

Abstract: RNA of the newly identified human metapneumovirus (HMPV) was detected in nasopharyngeal aspirates of 11 of 63 (17.5%) young children with respiratory tract disease. Markers of infection caused by another member of the Pneumovirinae subfamily of the family Paramyxoviridae, respiratory syncytial virus (RSV), were identified in 15 of these patients (23.8%). Three patients were simultaneously infected with HMPV and RSV. Studies of the clinical characteristics of HMPV-infected children did not reveal any difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
126
4
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(163 citation statements)
references
References 9 publications
23
126
4
10
Order By: Relevance
“…The rate of dual infection in our study population was similar to that observed in the Spanish study (26%) [29]. While data from other reports suggest that dual infection with hMPV and other respiratory viruses is rare (68-71) [6,29,30], both this study and the Spanish study [29] have demonstrated relatively high co-infection rates.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The rate of dual infection in our study population was similar to that observed in the Spanish study (26%) [29]. While data from other reports suggest that dual infection with hMPV and other respiratory viruses is rare (68-71) [6,29,30], both this study and the Spanish study [29] have demonstrated relatively high co-infection rates.…”
Section: Discussionsupporting
confidence: 46%
“…While data from other reports suggest that dual infection with hMPV and other respiratory viruses is rare (68-71) [6,29,30], both this study and the Spanish study [29] have demonstrated relatively high co-infection rates. Taking into account our observations on the occurrence of dual infections caused by both hMPV and other viruses, one might presume that a preselection of patients negative for other respiratory viruses could lead to an underestimation of the true incidence of hMPV infection.…”
Section: Discussionmentioning
confidence: 50%
“…Since then, hMPV has been identified worldwide and co-circulation of different hMPV genotypes can occur in the same geographical area. 2,3 So far, real-time PCR has been the preferred diagnostic method to detect hMPV.…”
Section: Introductionmentioning
confidence: 99%
“…Also, many studies have demonstrated that HMPV causes a respiratory tract infection clinically indistinguishable from infections caused by respiratory syncytial virus (RSV) and influenza. [1][2][3][4][5] In contrast, the specific prevention options and some populations severely affected vary for HMPV, RSV, and influenza. 7 Currently there is no vaccine for HMPV.…”
mentioning
confidence: 99%
“…[2][3][4][5] Infection with HMPV has been associated with an estimated 20 000 U.S. hospitalizations annually among children aged <5 years. 6 However, the infrequent testing and low index of suspicion associated with HMPV may have limited the assessment of temporal trends in HMPV circulation.…”
mentioning
confidence: 99%